(untitled) (Revista Contexto & Saúde, 2026)
Objective: To analyze expenses related to cancer treatment during the Covid-19 pandemic in the state of Ceará. Method: A descriptive study using expense records from the Ceará Hospital Information and High Complexity Procedure Authorization System, developed in 2022. The data were synthesized using Microsoft Excel 2019®. The following measures were used for descriptive analysis: means, standard deviation, minimums, maximums, and an estimate of the mean treatment cost. Results: A reduction in expenses was identified in 2020 (R 3,879,505.41) and 2021 (R 3,088,822.14) compared to 2019. In 2020, the reduction occurred in May (R 2,739,116.44) and June (R 2,633,173.82). In 2021, the months included February (R 3,193,095.98), April (R 3,093,272.64), and May (R 3,093,272.64). Surgery reduced the mean values ​​per procedure in 2020 and 2021 (R 3,626,046.22; R 3,545,102.89), followed by radiotherapy in 2020 (R 166,656.00) and chemotherapy (R 76,320.89) in 2020, with "adjuvant" treatment being reduced in both years (R 95,256.00; R 60,710.50). Conclusion: There was a slight reduction in expenses per procedure compared to pre-pandemic levels, but with a relevant assessment considering possible unmet demand during the pandemic.